A geodetic study of the Alpine Fault through South Westland: using campaign GPS data to model slip rates on the Alpine Fault. Issue 3 (3rd July 2018) - Page, Chris J.; Denys, Paul H.; Pearson, Chris F.
ABSTRACT: Although the Alpine Fault has been studied extensively, there have been few geodetic studies in South Westland. We include a series of new geodetic measurements from sites across the Haast Pass and preliminary results from a recently established network, the Cascade array that extends from the Arawhata River to Lake McKerrow, a region that previously had few geodetic measurements. We compare the slip rates based on models that include both single and double faults, and consider Alpine Fault dips of 55° and near vertical. Our preferred solution models the Alpine Fault as an infinitely long fault, dipping at 55° with a second (proxy) fault to account for (inboard) distributed deformation. This gives results that are consistent with the Alpine Fault being a predominantly strike-slip fault with a slip rate of 30 ± 2 mm/yr and therefore demonstrates that the slip rate of the Alpine Fault is constant along strike. The locking depth for the fault in this region is c. 17 km. Assuming a near vertical dip angle results in unrealistic high slip rates.